A proper concentration of carbon black nanoparticles enhances growth of the regenerated vetiver grass - Khunchuay, Chonnikarn; Sompornpailin, Kanokporn (My University, 2017)
Carbon black (CB) nanoparticles were used in enhancing efficiency of the plant regeneration process under tissue culture condition. The calli of vetiver grass (Vetiveria zizanioides L. Nash) were induced by using axillary bud as the explant. These calli were subjected onto plant regeneration medium, Murashige & Skoog (MS) medium supplemented with 1 mgL-1 α-naphthalene acetic acid (NAA), 2 mgL-1 6-benzylaminopurine (BAP) and 2 mgL-1 kinetin, adding 0-70 mgL-1 concentrations of carbon black (CB) nanoparticles. After six week incubation, vetiver calli developed on the medium supplemented with 40 mgL-1 CB nanoparticles showed the rather high frequencies of plant regeneration (93.75%), nevertheless no statistically different with other treatment did. Media containing CB nanoparticles in the range 40-60 mgL-1 significantly affected on enhancing the average of shoot number per callus more than other CB concentration did. Especially, the average shoot lengths of plantlets derived from 40 and 50 mgL-1 CB media (1.73 and 2.19 cm) are longer than those from non CB or other CB concentration media (0.88-1.05 cm) at the significant level. Adding CB nanoparticles in regeneration medium effects on enhancing electrical conductivity and decreasing the pH value. The concentration of CB nanoparticle effected the ratio of colloidal sizes which was found in the medium. The proper concentration of CB generates the optimum property of the regeneration medium which can promote the average of shoot number per callus, and enhanced shoot elongation of vetiver grass in the regeneration process.
Keywords: Carbon black; Nanoparticles; Plant growth; Plant regeneration; Vetiver grass